Philosophy of prognosis in surgery - N. A. Kuznetsov (Сеченовский вестник, 2014)
The author using a multidisciplinary approach (involving philosophy, mathematics, applied statistics and psychology) has solved a number of theoretical issues of clinical surgery in this article. On the basis of the philosophical (theoretical and, therefore, universal) definition of risk he describes the features of decision-making in routine and emergency surgery, proves the theoretical possibility of predicting the outcomes of the planned surgical intervention and the inability to anticipate the results of emergency surgery.